THE USE OF K-W-L (KNOW – WANT to KNOW – LEARNED) STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION - Saepudin Saepudin (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2018)
AbstractThe objectives of this research are: (1) finding out whether and to what extent KWL (Know - Want to Know - Learned) Strategy can improve reading ability of sixth grade students of SD Negeri Buaranjati I and (2) describing what happens to classroom situation when KWL Strategy is applied in teaching reading. The subjects of the research are twenty eight students of class 6th SD Negeri Buaranjati I. The research data were obtained by using several techniques including: test, observation, interview, questionnaire, field notes and photographs. The quantitative data were analyzed by using descriptive statistic. Mean while, qualitative data were analyzed by using 5 stages suggested by Burns (1999: 157- 159) consisting of: assembling the data; coding the data; comparing the data; building interpretation; and reporting the outcomes. The research findings show that the use of KWL Strategy could improve students’ reading ability and classroom situation of English class. The improvement of students’ reading comprehension can be seen from the improvement of the mean score of pre-test, first post-test, and second post-test, that is 66.95; 75.43 and 80.65.Keywords: K-W-L strategy, Know – Want to Know – Learned, reading comprehension AbstrakTujuan penelitian ini adalah: (1) mengetahui apakah strategi KWL (Know-Want to Know- Learned) dapat meningkatkan kemampuan membaca siswa kelas 6 SDN Buaranjati I dan (2) untuk mendeskripsikan bagaimana situasi dalam kelas ketika strategi KWL digunakan dlam pembelajaran membaca. Sampel penelitian ini adalah 28 siswa kelas 6 SDN Buaranjati I. Data penelitian dideroleh menggunakan beberapa Teknik seperti tes, observasi, wawancara, catatan lapangan, dan dokumentasi foto. Data kuantitatif dianalisis menggunakan statistik deskriptif. Sedangkan, data kualitatif dianalisis melalui lima langkah menurut Burns (1999) yang terdiri dari mengumpulkan data; mengkode data; membandingkan data; membangun interpretasi; dan melaporkan hasilnya Temuan penelitian ini menunjukkan bahwa startegi KWL dapat meningkatkan kemampuan membaca komprehensi siswa. Peningkatan ini dapat dilihat dari peningkatan nilai pre-tes, pos-tes pertama, dan postes kedua, yaitu 66.95; 75.43, dan 80.65.Kata Kunci: K-W-L, Know – Want to Know – Learned, membaca komprehensif